Public–Private Partnerships in the Preservation of Presidential Records. Issue 2 (February 2021) - Boden, Daniel; Exmeyer, Patrick C.
The National Archives and Records Administration, in partnership with private support foundations, administers 13 individual presidential libraries comprising the Presidential Library System. These privately constructed, publicly supported archives not only preserve official presidential records but through their museum displays offer visitors a glimpse into the life and times of specific presidents. Utilizing legislation, archival documents, and elite interviews to characterize governance and administration structures of these relationships, this study outlines the nature of current public–private partnerships within the Presidential Library System, as well as the potential departure from existing frameworks for future partnerships absent formalized guidance procedures.